The Effect Social Skills Training on Pre-school Children's Emotional Intelligence & Social Skills - Machmudah; Eva, Nur; Andrini Farida, Ika; Akbar, Sa'dun; Hidayah, Rifa; Hanurawan, Fattah; Chusniyah, Tutut; Fitriyah, Fifi Khoirul (Jurnal Pendidikan Anak, 2024)
Teachers play an important role in enhancing the emotional intelligence and social skills of early childhood children, so teachers need to have the skills to teach emotional intelligence and social skills to their students. This study aims to empirically test whether social skills training interventions affect children's emotional intelligence and social skills. The type of research is an experimental study with a pretest-posttest group design. The population and sample of the study are students from 2 kindergarten schools in Sidoarjo, totaling 60 students, using purposive sampling. Participants attended social skills training sessions totaling seven, with each session lasting 60-120 minutes. Data collection techniques used questionnaires (EISC & SSS) and documentation. https://jurnal.umsu.ac.id/lib/journal/ The data analysis technique used is regression analysis. From the data analysis conducted, the pre-test and post-test results obtaine for emotional intelligence and 0.051 for children's social skills. The research results prove that there is an influence of social skills training on emotional intelligence and social skills in early childhood.